Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Pengangguran Dan Inflasi di Kabupaten Gorontalo - Muhammad Hamzah Anas; Reski Handayani; Sriwahyuni Lamalai; Muhammad Ersa Ayub Pakaya (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
Unemployment and inflation are two main issues that affect economic and social stability in Gorontalo Regency. This study aims to analyze the factors that influence unemployment and inflation rates in the region. Qualitative research methods were used by conducting in-depth interviews with various stakeholders, including workers, entrepreneurs and district governments. The results of the analysis show that factors such as lack of workforce skills, lack of available jobs, rising production costs, and fluctuations in commodity prices contribute to high levels of unemployment and inflation. Evaluation of the limitations of previous studies reveals that the lack of in-depth analysis of the factors underlying these two issues is one of the main weaknesses. Based on the research results, it is recommended that local governments adopt a holistic and integrated approach in overcoming these two problems, by strengthening cross-sector collaboration and implementing effective policies in controlling inflation and increasing employment opportunities. Further research needs to be conducted to evaluate the impact of implementing the proposed policies over a longer period.